2021
DOI: 10.1016/j.bonr.2021.101123
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiome depletion and repetitive mild traumatic brain injury differentially modify bone development in male and female adolescent rats

Abstract: Dysregulation of the gut microbiome has been shown to disrupt both bone formation and bone resorption in several preclinical and clinical models. However, the role of microbiome in adolescent bone development remains poorly understood. This effect of disrupted bone development may be more pronounced during adolescence, when bone development is vulnerable to environmental stimuli and external insults (e.g., antibiotic treatment and traumatic brain injury), as this is a critical window of development. Therefore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…First, our findings demonstrate a microbial maturational change in adolescents that reach adult levels by P51, but a stability over the experimental time frame for adult rats. Given that depletion of the gut microbiome is a common modality utilised to investigate the role of the microbiome [ 43 ], we used 14-day antibiotic administration prior to injury, as a mechanism to determine if the microbiome is involved in mTBI pathophysiology, and how microbiome diversity and functionality recovers in the context of RmTBI. Second, we demonstrate that microbiome depletion significantly modified the adolescent microbiome and metabolome, both at the acute and chronic timepoints of our examination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, our findings demonstrate a microbial maturational change in adolescents that reach adult levels by P51, but a stability over the experimental time frame for adult rats. Given that depletion of the gut microbiome is a common modality utilised to investigate the role of the microbiome [ 43 ], we used 14-day antibiotic administration prior to injury, as a mechanism to determine if the microbiome is involved in mTBI pathophysiology, and how microbiome diversity and functionality recovers in the context of RmTBI. Second, we demonstrate that microbiome depletion significantly modified the adolescent microbiome and metabolome, both at the acute and chronic timepoints of our examination.…”
Section: Discussionmentioning
confidence: 99%
“…In preclinical studies, the administration of a broad-spectrum antibiotic cocktail over a 14-day period is commonly utilized as a method of depleting enteric bacteria with low systemic absorption [ 38 , 43 , 55 , 56 ]. However, there have been no studies that have investigated this on the adolescent microbiome and its comparative effects to adults.…”
Section: Discussionmentioning
confidence: 99%
“…Given the findings of microbiome changes after TBI, some studies sought to investigate potential connections between dysbiosis and bone formation, post-traumatic epilepsy, neurologic outcomes, and post-traumatic stress disorder. One group investigated dysbiosis after TBI and found that pre-injury microbiome-depleted rats had disruption of femur growth, with different aspects of growth irregularities between males and females [ 42 ]. Another study showed that post-traumatic epilepsy can be stratified based on microbial composition [ 30 ].…”
Section: Traumamentioning
confidence: 99%
“…To do so, we induced microbiome depletion via systemic administration of a broad-spectrum antibiotic cocktail prior to RmTBI induction in adolescent and adult rats. 27 Socio-emotional functioning was analyzed via play behavior and temperament analysis, as well as comorbid measures including anxiety-like behavior and alterations to pain sensitivity. We hypothesized that adolescent rats exposed to microbiome depletion and RmTBI would demonstrate worsened socio-emotional functioning compared to adult rats, and that these deficits would be associated with reductions in PNNs, PVs, and PNN arborization within the mPFC and OFC.…”
Section: Introductionmentioning
confidence: 99%